Effect of woven veneer on the mechanical properties of oil palm plywood - Ab Kadir, Helmi Fariz (2016)
Oil palm is the one of the largest agriculture in Malaysia. So that, oil palm farm in Malaysia produce so much oil palm trunk that have potential to be used to replace wood. So that, commercializing oil palm trunk was the best way in order to avoid wasted. To prove this fact, the study to test the strength of the plywood made from oil palm trunk. The objective of this study is to provide basic information after the power trunks are made of plywood in the fabrication of the seven types and to compare the strength of seven different types of fabrication. Seven types of fabrication are 'OWOWOW', 'OWONOW', 'ONOWON', 'OWVOW', 'VOWV', 'OW'OW'OW' 'and' N'N'N ''. A total of 105 samples were made according to seven fabrications that being tested. Data were analyzed using SPSS 22.0 to find the balance of power between seven fabrications. Results through bending tests prove that 'VOWV' is a very strong resistance with the value of MOE was 1029.15(±80.7084) and value of MOR was 9.279334(±0.4825) while 'N'N'N' too weak immune strength. Similarly, IB test of strength 'VOWV' still proved robust compared with six other fabrications with the value 9.47061(±1.4739).